Gamifying Vocabulary Learning: Teachers’ Perceptions on The Implementation of Gimkit for Junior High School - Mochammad Syaifullah; Sonny Elfiyanto (Universitas Cokroaminoto Palopo, 2026)
This research explores junior high school teachers’ perceptions of using Gimkit as a game-based platform for vocabulary learning. A qualitative research design was employed, with data collected through in-depth interviews and classroom observations involving three English teachers at a junior high school in Malang City who had experience implementing Gimkit in their classes. The findings indicate that teachers generally hold positive perceptions of Gimkit, as it helps increase students’ motivation, engagement, and vocabulary retention through interactive and competitive features. Teachers also appreciate the platform’s flexibility, which enables them to tailor learning activities to meet students’ needs. However, several challenges were identified, particularly related to unstable internet connections and limited technological infrastructure in schools. Overall, the research suggests that Gimkit can be an effective tool for supporting vocabulary instruction at the junior high school level. Future research is recommended to examine its impact on students’ learning outcomes and to develop practical guidelines for its effective implementation in classroom contexts.